Corner-Store Dreams and the 2008 Financial Crisis A True Story about Risk, Entrepreneurship, Immigration, and Latino-Anglo Friendship - Wogan, Peter (Palgrave Studies in Literary Anthropology, 2017)
XII, 229 p.